Transformational Leadership, Workload, and Entrepreneurial Motivation in Increasing Organizational Commitment: Kepemimpinan Transformasional, Beban Kerja, dan Motivasi Berwirausaha dalam Meningkatkan Komitmen Organisasi - Maufuzah, Intan Anis; Abadiyah, Rifdah (Universitas Muhammadiyah Sidoarjo, 2023)
The purposed of the following study are to analyze and describe the impact of transformational leadership variables, workload, and entrepreneurial motivation on organizational commitment in IKM tas UD. Suwarlandono Tanggulangin. In this study, using quantitative research methods, data collection was distributed through a questionnaire/questionnaire, with a sample using a saturated sample, where there were 170 respondents in IKM bag UD. Suwarlandono Tanggulangin. The data analysis used multiple linear regression test, asumsi classic test, , and also hypothesis testing, namely partial and simultaneous tests, and data management using SPSS version 22 software. Primary data collection was carried out by distributing questionnaires which were measured using an interval scale, the testing used Validity and Reliability Test. This study proves that transformational leadership, workload, and entrepreneurial motivation have a partial or simultaneous influence on organizational commitment.